Agricultural carbon reduction effects of the ecological circular agriculture pilot - WANG Wei, MAO Wei, XIAO Hua, ZHANG Weikun (Ziyuan Kexue, 2025)
[Objective] How to promote carbon reduction and sequestration in agriculture and rural areas from the macro policy level is a topic of great concern. As an important institutional design for promoting the modernization of agriculture and rural areas, the pilot policy of ecological circular agriculture should have a profound impact on agricultural carbon reduction. The extent of its impact and the mechanism of action deserve in-depth study. [Methods] Based on clarifying the mechanism by which the pilot policy of ecological circular agriculture affects agricultural carbon emission reduction, this paper conducts quasi-natural experiments with the pilot policy of ecological circular agriculture. Based on the balanced panel data of 31 provinces in China from 2000 to 2021, The impact of the pilot policy of ecological circular agriculture on agricultural carbon emission reduction and the spatial spillover effect were systematically investigated by using the regression control method, synthetic control method and difference-in-differences method. [Results] (1) Overall, the pilot policy of ecological circular agriculture significantly reduced the value of agricultural carbon emissions and had a significant inhibitory effect on agricultural carbon emissions in the three pilot provinces of Zhejiang, Anhui and Hainan. Moreover, the benchmark results remained valid after a series of robustness tests; (2) Based on the framework of “scale-structure-technology”, the mechanism test results show that the pilot policy of ecological circular agriculture mainly has an impact on agricultural carbon emission reduction from three aspects: agricultural operation scale, agricultural planting structure and agricultural scientific and technological progress; (3) The results of the spatial spillover effect show that the pilot policy of ecological circular agriculture has a significant promoting effect on agricultural carbon reduction in this region and neighboring regions. [Conclusion] The pilot policy of ecological circular agriculture has great potential for reducing carbon emissions in agriculture and provides theoretical basis and practical support for the promotion of the pilot policy. It is suggested to promote moderate-scale agricultural operations, optimize the agricultural planting structure, and strengthen the support of agricultural science and technology and equipment, so as to accelerate the comprehensive green transformation of agricultural development.